A cobalt tetroxide supercapacitor positive electrode material and preparation method thereof and supercapacitor
The positive electrode material of cobalt tetroxide supercapacitor is prepared by co-precipitation method, and modified NiO is added after calcination. This solves the problems of supercapacitor in terms of cycle stability, energy density and self-discharge, and achieves better electrochemical performance and capacity retention. Rate.
Patent Information
- Application Number
- CN202411629907.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-11-15
AI Technical Summary
Supercapacitors have problems with cycle stability, energy density and self-discharge, making it difficult to surpass the performance of the battery.
COHCC is prepared through the common precipitation method, and then cOHCC is used as the front -drive body to obtain a tetraonic oxidation triple cobalt super capacitor positive material through high temperature 煅, and the modified NIO is incorporated in oxides to improve the electrochemical performance.
The excellent electrochemical properties and high capacity maintenance rates of the tetraxide triangular supercapacitors positive materials are achieved, which improves its energy density and cycle stability.
Smart Images

Figure CN119132846B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of supercapacitors, and more specifically, relates to a cobalt tetroxide supercapacitor positive electrode material and a preparation method thereof and a supercapacitor. Background Art
[0002] Supercapacitors, a new type of energy storage device, transcend the boundaries between traditional chemical energy storage power sources and conventional capacitors and batteries. It mainly stores electrical energy through the charge and discharge mechanism of redox pseudocapacitors and double-layer capacitors, which enables it to undergo hundreds of thousands of cycles of charge and discharge without failure. The basic principle of its energy storage is the same as other double-layer capacitors, that is, high capacity is achieved by using the double-layer structure composed of activated carbon porous electrodes and electrolytes. Supercapacitors surpass batteries with their excellent power performance, especially good at fast charging and discharging under high currents. However, despite this, batteries of the same volume still have higher energy density and storage capacity.
[0003] Compared with traditional chemical power sources, supercapacitors are new energy storage devices between capacitors and batteries. Their charging method relies on redox pseudocapacitors and double-layer capacitors. Since their energy storage process is chemically reaction-free and reversible, they can be charged and discharged multiple times. Their basic principle is still the double-layer capacitor structure composed of activated carbon porous electrodes and electrolytes, which provides a large capacity. In comparison, supercapacitors are superior to batteries in terms of power characteristics and have fast and high current charging and discharging capabilities. Although under the same conditions, batteries have slightly better energy density and larger capacity. With the rapid development of the electronics industry, the requirements of electronic equipment for power sources are constantly increasing, which undoubtedly promotes the research and development of new power sources. On the other hand, the intensification of the global energy crisis has aroused people's attention to clean energy. The rise of new energy and the widespread application of energy-saving technologies have made the application scope of supercapacitors increasingly broad.
[0004] Despite this, supercapacitors have always been unable to surpass batteries and have not been able to fully realize their potential due to problems such as weak cycle stability, low energy density, and severe self-discharge. Currently, the main strategy to solve the energy density problem of supercapacitors is to use a hybrid battery-supercapacitor combination. This type of structure combines the high power performance of supercapacitors with the high energy density of secondary batteries, and has the characteristics of long life and low cost. With the advancement of technology, hybrid supercapacitors with higher power density and higher energy density are expected to emerge. In this context, supercapacitors are expected to compete fiercely with secondary batteries.
[0005] The transition metal cobalt is located in the fourth period and fifth subgroup. Its unique chemical activity gives it a rich variety of valence states, and it can form many cobalt-based compounds with different valence states, among which +2 and +3 valence compounds are the most common. Cobalt-based oxides, sulfides, and hydroxides are all easy-to-prepare compounds with excellent performance. They have shown excellent electrochemical activity in the field of electrochemical energy storage, so they are widely used in this field and have become pseudocapacitor positive electrode materials with great development potential.
[0006] Among the many cobalt oxides that have been studied for use as supercapacitor electrode materials, Co3O4 has become the most intensively studied cobalt oxide variety due to its high specific capacity. During the charging process, the positive and negative ions in the electrolyte are adsorbed on the surface of the cobalt oxide electrode under the action of the electric field, forming a stable double-layer structure. This double-layer structure can store a large amount of charge, thereby achieving a high energy density of the capacitor. As a typical pseudocapacitor material, cobalt oxide undergoes a reversible redox reaction on its surface during the charging and discharging process, which can produce additional capacitance.
[0007] As a new type of high-quality energy storage device, supercapacitors have great market application prospects, but currently supercapacitors face problems such as weak cycle stability, low energy density, and severe self-discharge. Electrode materials directly affect the electrochemical performance of supercapacitors and can be used as the core entry point for such problems. Prussian blue analogs, as a typical metal organic framework material, have attracted widespread attention when used as supercapacitor electrode materials due to their advantages such as fast charging and discharging, high power density, and environmental friendliness. Cobalt-based oxides can exhibit good electrochemical activity as electrode materials and can quickly undergo redox reactions with electrolytes to produce capacitance. Summary of the invention
[0008] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.
[0009] In order to achieve these purposes and other advantages according to the present invention, a method for preparing a cobalt oxide supercapacitor positive electrode material is provided, comprising the following steps:
[0010] Step 1, add Co(NO3)2·6H2O, Na3C6H5O7·2H2O and polyvinylpyrrolidone into deionized water and mix well to obtain solution A;
[0011] Step 2: Add K3[Co(CN)6] to deionized water and mix thoroughly to obtain solution B;
[0012] Step 3: At room temperature, solution B is added dropwise to solution A, mixed thoroughly and allowed to stand to obtain a pink precipitate. After multiple centrifugation and washing the pink precipitate with deionized water, the pink precipitate is dried in an oven to obtain a precursor CoHCC.
[0013] Step 4: Place the precursor CoHCC in a muffle furnace, set a temperature increase program, and keep the temperature to obtain a cobalt tetroxide supercapacitor positive electrode material.
[0014] Preferably, in step 1, the ratio of Co(NO3)2·6H2O, Na3C6H5O7·2H2O, polyvinyl pyrrolidone and deionized water is 0.6mmol:0.8~1.2mmol:0~0.1g:20~50mL.
[0015] Preferably, in step 2, the usage ratio of K3[Co(CN)6] to deionized water is 0.3~0.6mmol:20~50mL.
[0016] Preferably, in step 3, the volume ratio of solution A to solution B is 1-2:1-2;
[0017] The standing time is 12~24h; the drying temperature is 60~90℃.
[0018] Preferably, in step 4, the temperature rising procedure is: heating to 500-800° C. at a rate of 1-5° C. / min, and the holding time is 1-4 h.
[0019] Preferably, in the step 4, after the precursor CoHCC is calcined in a muffle furnace, modified NiO is added to the oxide obtained by calcination, and the modified NiO accounts for 0-15% of the mass of the precursor CoHCC; the preparation method of the modified NiO comprises:
[0020] S11, dispersing NiO powder in a glucose aqueous solution to obtain a mixed dispersion, wherein the mass volume ratio of NiO powder to the glucose aqueous solution is 0.5-1 g:50-80 mL, and the concentration of the glucose aqueous solution is 0.15-0.3 mol / L; dispersing graphene in deionized water to obtain a graphene dispersion, wherein the mass volume ratio of graphene to the mixed dispersion is 0.1-0.3 g:20-40 mL;
[0021] S12, mixing the mixed dispersion with a graphene dispersion of half its volume, transferring to an autoclave, setting the heating temperature, pressure and reaction time, cooling to room temperature after the reaction is completed, separating the solid from the liquid to obtain a solid product, and vacuum drying to obtain graphene-modified NiO powder;
[0022] S13, dispersing graphene-modified NiO powder in deionized water to obtain dispersion A; dispersing nano-MnO2 powder with a particle size of 5-8 nm in dispersion A, adding polyvinyl pyrrolidone, magnetically stirring for 1-3 h, heating to 60-80° C., keeping the temperature for 20-60 min, cooling to room temperature, centrifuging, and vacuum drying to obtain a mixed powder;
[0023] S14, subjecting the mixed powder to a static press at 6-8 MPa for 5-10 seconds and then subjecting it to a heat treatment, specifically comprising: placing the mixed powder in a resistance furnace, in an argon or nitrogen atmosphere, heating the mixture to 400-500°C at a heating rate of 5-10°C, keeping the mixture at that temperature for 1-3 hours, cooling the mixture to 100-200°C at a cooling rate of 5-10°C, keeping the mixture at that temperature for 3-6 hours, and finally cooling the mixture with the furnace to obtain modified NiO.
[0024] Preferably, in S12, the heating temperature is set to 200-230° C., the pressure is set to 2.5-3.6 MPa, and the reaction time is set to 8-10 h;
[0025] In the S13, the usage ratio of graphene-modified NiO powder, deionized water, nano-MnO2 powder, and polyvinyl pyrrolidone is 1~5g:100~250mL:0.1~0.5g:0.05~0.2g.
[0026] Preferably, the method of adding modified NiO to the oxide obtained by calcining the precursor CoHCC is dry ball milling mixing, using zirconium oxide as grinding balls, the mass of the grinding balls is 1 to 2.5 times the total mass of the modified NiO and the oxide obtained by calcining the precursor CoHCC, the ball milling time is 1 to 6 hours, and the ball milling speed is 500 to 1000 rpm.
[0027] A cobalt tetroxide supercapacitor positive electrode material is prepared by the cobalt tetroxide supercapacitor positive electrode material preparation method.
[0028] A supercapacitor comprises the above-mentioned cobalt tetroxide supercapacitor positive electrode material.
[0029] The present invention has at least the following beneficial effects:
[0030] The present invention prepares CoHCC by a coprecipitation method, and then obtains a cobalt tetroxide supercapacitor positive electrode material by high-temperature calcination using CoHCC as a precursor. The results show that the cobalt tetroxide supercapacitor positive electrode material prepared by the method using Na3C6H5O7·2H2O as a complexing agent and polyvinyl pyrrolidone as a surfactant has excellent electrochemical performance and extremely high capacity retention rate. After the cobalt tetroxide supercapacitor positive electrode material of the present invention and activated carbon as a negative electrode are used to construct an asymmetric supercapacitor, the supercapacitor has extremely high energy density, which is due to the fact that the cobalt tetroxide supercapacitor positive electrode material can provide a large surface area for full contact with an electrolyte, excellent electrical conductivity and rapid charge transfer capability, thereby improving the problems of low long-cycle stability and low energy density of the supercapacitor.
[0031] At the same time, the present invention also doped 0-15% of modified NiO into the oxide (Co3O4) obtained by calcining the precursor CoHCC. The results showed that compared with conventional NiO-doped and non-NiO-doped, the doping of modified NiO further improved the electrochemical properties of the cobalt tetroxide supercapacitor positive electrode material, thereby further improving the capacity retention rate of the cobalt tetroxide supercapacitor positive electrode material. After the cobalt tetroxide supercapacitor positive electrode material and activated carbon were used as the negative electrode to construct an asymmetric supercapacitor, the energy density of the supercapacitor was further improved.
[0032] Among them, in the preparation process of modified NiO, NiO is first used to undergo hydrothermal carbonization reaction with glucose and graphene to complete the carbon loading and graphene modification on the NiO surface, and then the surfactant is dispersed and combined with MnO2 in dispersion A to coat the surface of the graphene-modified NiO with MnO2, and then the tightness of the combination of MnO2 and NiO is improved by static pressure and heat treatment. This method of sequentially coating graphene and MnO2 through two dispersions, the prepared modified NiO has a larger surface area and better electrochemical properties. After the modified NiO is doped with the oxide calcined by the precursor CoHCC, a cobalt tetroxide supercapacitor positive electrode material with further improved electrochemical properties is obtained.
[0033] The advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a SEM image of the cobalt tetroxide supercapacitor positive electrode material prepared in Example 1;
[0035] Figure 2 This is a SEM image of the cobalt tetroxide supercapacitor positive electrode material prepared in Comparative Example 1;
[0036] Figure 3 The XRD spectrum of the cobalt tetroxide supercapacitor positive electrode material prepared in Example 1;
[0037] Figure 4 The cobalt tetroxide supercapacitor positive electrode materials prepared in Example 2, Example 4, Example 5 and Comparative Example 1 have a 0-0.5V range and a 50mV s -1 Cyclic voltammograms under
[0038] Figure 5 Constant current charge and discharge curves of the cobalt tetroxide supercapacitor positive electrode materials prepared in Example 2, Example 4, Example 5 and Comparative Example 1;
[0039] Figure 6 The AC impedance curves of the cobalt tetroxide supercapacitor positive electrode materials prepared in Example 2, Example 4, Example 5 and Comparative Example 1;
[0040] Figure 7 Cyclic voltammetry curves of cobalt tetroxide supercapacitor positive electrode materials prepared in Example 2, Example 4, Example 5 and Comparative Example 1 at different scan rates;
[0041] Figure 8 Constant current charge and discharge curves of the cobalt tetroxide supercapacitor positive electrode materials prepared in Example 2, Example 4, Example 5 and Comparative Example 1 at different current densities;
[0042] Fig. 9 The relationship diagram between the specific capacity and the current density of the cobalt tetroxide supercapacitor positive electrode material prepared in Example 2 and Comparative Example 1;
[0043] Fig.10 The cobalt tetroxide supercapacitor positive electrode material prepared in Example 2 and Comparative Example 1 is 100 mV s -1 The retention rate curve of 2000 cycles of charge and discharge at a scan rate of;
[0044] Fig.11 YP50 of activated carbon at 1A g -1 Constant current charge and discharge curve under ;
[0045] Fig.12 The cyclic voltammetry curves of the cobalt tetroxide supercapacitor positive electrode material and activated carbon YP50 prepared in Example 2;
[0046] Fig.13 Cyclic voltammetry curves of the Co3O4 / / AC electrodes constructed by the cobalt tetroxide supercapacitor positive electrode material prepared in Example 2 and activated carbon YP50 at different scan rates;
[0047] Fig.14Constant current charge-discharge curves of the Co3O4 / / AC electrodes constructed by the cobalt oxide supercapacitor positive electrode material prepared in Example 2 and activated carbon YP50 at different current densities;
[0048] Fig.15 This is the relationship between the specific capacity of the Co3O4 / / AC two electrodes and the current density;
[0049] Fig.16 This is the relationship between the energy density and specific power of the two electrodes of Co3O4 / / AC;
[0050] Fig.17 It is the impedance curve of Co3O4 / / AC two electrodes;
[0051] Fig.18 For Co3O4 / / AC, the two electrodes are at 100mV s -1 The retention rate change diagram of long cycle charge and discharge test under the condition of
[0052] Fig.19 For Co3O4 / / AC, the two electrodes are at 100mV s -1 Long cycle charge-discharge voltammogram under . DETAILED DESCRIPTION
[0053] The present invention is further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.
[0054] It should be understood that terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.
[0055] Example 1
[0056] This embodiment provides a method for preparing a cobalt oxide supercapacitor positive electrode material, comprising the following steps:
[0057] Step 1: Add 0.6 mmol Co(NO3)2·6H2O, 0.08 mmol Na3C6H5O7·2H2O and 0.05 g polyvinylpyrrolidone into 20 mL deionized water and mix thoroughly to obtain solution A;
[0058] Step 2: Add 0.04 mmol K3[Co(CN)6] to 20 mL deionized water and mix thoroughly to obtain solution B;
[0059] Step 3: At room temperature, solution B was added dropwise to solution A, mixed thoroughly and allowed to stand for 24 hours to obtain a pink precipitate. After multiple centrifugation and washing the pink precipitate with deionized water, the pink precipitate was dried in an oven at 80°C for 30 minutes to obtain the precursor CoHCC.
[0060] Step 4: Place the precursor CoHCC in a muffle furnace and heat it to 500° C. at 2° C. / min and keep it at that temperature for 2 h to obtain the cobalt tetroxide supercapacitor positive electrode material.
[0061] Example 2
[0062] This embodiment provides a method for preparing a cobalt tetroxide supercapacitor positive electrode material. Compared with Example 1, the difference is that the amount of Na3C6H5O7·2H2O in step 1 is 1 mmol, and the process parameters of the remaining steps are the same as those in Example 1.
[0063] Example 3
[0064] This embodiment provides a method for preparing a cobalt tetroxide supercapacitor positive electrode material. Compared with Example 1, the difference is that the amount of Na3C6H5O7·2H2O in step 1 is 1.2 mmol, and the process parameters of the remaining steps are the same as those in Example 1.
[0065] Example 4
[0066] This embodiment provides a method for preparing a cobalt tetroxide supercapacitor positive electrode material. Compared with Example 2, the amount of polyvinyl pyrrolidone used in step 1 is 0.075 g, and the process parameters of the remaining steps are the same as those in Example 2.
[0067] Example 5
[0068] This embodiment provides a method for preparing a cobalt tetroxide supercapacitor positive electrode material. Compared with Example 2, the amount of polyvinyl pyrrolidone used in step 1 is 0.1 g, and the process parameters of the remaining steps are the same as those in Example 2.
[0069] Example 6
[0070] This embodiment provides a method for preparing a cobalt oxide supercapacitor positive electrode material. Compared with Example 2, the oxide obtained by calcining the precursor CoHCC in step 4 is doped with modified NiO accounting for 10% of the mass of the precursor CoHCC, thereby obtaining a cobalt oxide supercapacitor positive electrode material; the method of doping the modified NiO is dry ball milling mixing, using zirconium oxide as a grinding ball, the mass of the grinding ball is twice the total mass of the oxide obtained by calcining the modified NiO and the precursor CoHCC, the ball milling time is 1h, and the ball milling speed is 600rpm. The process parameters of the remaining steps are the same as those of Example 2.
[0071] Wherein, the modified NiO is NiO co-modified with graphene and manganese dioxide, and the preparation method of the modified NiO includes:
[0072] S11, dispersing 10g of NiO powder in 500mL of glucose aqueous solution to obtain a mixed dispersion, wherein the concentration of the glucose aqueous solution is 0.3mol / L; dispersing 1g of graphene in 250mL of deionized water to obtain a graphene dispersion;
[0073] S12, 500 mL of the mixed dispersion was mixed with 250 mL of the graphene dispersion, and the mixture was transferred into an autoclave, and the heating temperature was set to 230° C. and the pressure was set to 3.6 MPa, and the reaction was performed for 8 h. After the reaction was completed, the mixture was cooled to room temperature, and the solid product was separated from the liquid and vacuum dried to obtain graphene-modified NiO powder;
[0074] S13, dispersing 5 g of graphene-modified NiO powder in 250 mL of deionized water to obtain dispersion A; dispersing 0.5 g of nano-MnO2 powder with a particle size of 5-8 nm in dispersion A, adding 0.1 g of polyvinyl pyrrolidone, stirring magnetically for 2 h, heating to 80 ° C, keeping warm for 40 min, cooling to room temperature, centrifuging, and vacuum drying to obtain a mixed powder;
[0075] S14, heat treating the mixed powder by using a static press at 8 MPa for 6 seconds, specifically comprising: placing the mixed powder in a resistance furnace, heating it to 500°C at a heating rate of 5°C in a nitrogen atmosphere, keeping it warm for 3 hours, cooling it to 150°C at a cooling rate of 5°C, keeping it warm for 4 hours, and finally cooling it with the furnace to obtain modified NiO.
[0076] Example 7
[0077] This embodiment provides a method for preparing a cobalt oxide supercapacitor positive electrode material. Compared with Example 2, the oxide obtained by calcining the precursor CoHCC in step 4 is doped with modified NiO accounting for 15% of the mass of the precursor CoHCC, thereby obtaining a cobalt oxide supercapacitor positive electrode material. The method of doping the modified NiO is dry ball milling mixing, using zirconium oxide as a grinding ball, the mass of the grinding ball is twice the total mass of the oxide obtained by calcining the modified NiO and the precursor CoHCC, the ball milling time is 1h, and the ball milling speed is 600rpm. The process parameters of the remaining steps are the same as those in Example 2.
[0078] Wherein, the modified NiO is NiO co-modified with graphene and manganese dioxide, and the preparation method of the modified NiO includes:
[0079] S11, dispersing 10 g of NiO powder in 500 mL of glucose aqueous solution to obtain a mixed dispersion, wherein the concentration of the glucose aqueous solution is 0.2 mol / L; dispersing 3 g of graphene in 250 mL of deionized water to obtain a graphene dispersion;
[0080] S12, 500 mL of the mixed dispersion was mixed with 250 mL of the graphene dispersion, and the mixture was transferred into an autoclave, and the heating temperature was set to 200° C., the pressure was set to 3.2 MPa, and the reaction time was set to 8 h. After the reaction was completed, the mixture was cooled to room temperature, and the solid-liquid separation was performed to obtain the resultant solid, and the resultant solid was dried to obtain graphene-modified NiO powder;
[0081] S13, dispersing 5g of graphene-modified vacuum-dried NiO powder in 250mL of deionized water to obtain dispersion A; dispersing 0.1g of nano-MnO2 powder with a particle size of 5-8nm in dispersion A, adding 0.1g of polyvinyl pyrrolidone, stirring magnetically for 1h, heating to 80°C, keeping warm for 40min, cooling to room temperature, centrifuging, and vacuum drying to obtain a mixed powder;
[0082] S14, subjecting the mixed powder to a static press at 6 MPa for 5 seconds and then subjecting it to a heat treatment, specifically comprising: placing the mixed powder in a resistance furnace, heating it to 500°C at a heating rate of 5°C in a nitrogen atmosphere, keeping it warm for 3 hours, cooling it to 100°C at a cooling rate of 5°C, keeping it warm for 6 hours, and finally cooling it with the furnace to obtain modified NiO.
[0083] Comparative Example 1
[0084] This comparative example provides a method for preparing a cobalt tetroxide supercapacitor positive electrode material. Compared with Example 2, polyvinyl pyrrolidone is not added in step 1, and the process parameters of the remaining steps are the same as those of Example 2.
[0085] Comparative Example 2
[0086] This comparative example provides a method for preparing a cobalt oxide supercapacitor positive electrode material. Compared with Example 6, unmodified NiO is used to replace modified NiO, and the process parameters of the remaining steps are the same as those of Example 2.
[0087] Comparative Example 3
[0088] This comparative example provides a method for preparing a cobalt oxide supercapacitor positive electrode material. Compared with the other examples 6, unmodified NiO, graphene and MnO2 are used to replace the modified NiO, wherein the total mass of the unmodified NiO, graphene and MnO2 accounts for 10% of the mass of the precursor CoHCC, and the mass proportion of the unmodified NiO, graphene and MnO2 is the same as the proportion of each component in Example 6, that is, the mass ratio of unmodified NiO, graphene and MnO2 is 10:1:1.1, and the mixing method of the oxides obtained by calcining the unmodified NiO, graphene and MnO2 with the precursor CoHCC is the same as the mixing method of the modified NiO with the calcined precursor CoHCC in Example 6, and the process parameters of the remaining steps are also the same as those in Example 6.
[0089] The cobalt tetroxide supercapacitor positive electrode materials prepared in Examples 1 to 7 and Comparative Examples 1 to 3 are respectively made into electrodes. The specific method is: mix the cobalt tetroxide supercapacitor positive electrode material with acetylene black and polyvinylidene fluoride in a mass ratio of 8:1:1, and place in a mortar. After fully grinding and mixing, put it in an oven and dry it at 80°C for 1h. Then weigh the mass of the mixed powder in a 10mL small beaker, add 3 to 4 drops of N-methyl-2-pyrrolidone as a solvent to the small beaker, stir well, and obtain electrode slurry. Dip the prepared electrode slurry with a brush and evenly apply it on an area of 1cm 2 The nickel foam coated with the electrode slurry is placed in a vacuum oven, and the temperature of the vacuum oven is set to 80° C. to vacuum dry to prepare a working electrode of the cobalt tetroxide supercapacitor positive electrode material.
[0090] like Figure 1 and Figure 2 As shown, the cobalt tetroxide supercapacitor positive electrode material prepared in Example 1 presents a uniform and regular cubic structure, and the nanocubes are dense in volume, providing favorable conditions for the full occurrence of redox reactions. However, the cobalt tetroxide supercapacitor positive electrode material prepared in Comparative Example 1 does not add polyvinyl pyrrolidone, and irregular cubes of uneven shapes and sizes appear, and the volume is large, which will have a certain impact on its electrochemical performance.
[0091] like Figure 3 As shown, sharp diffraction signals can be clearly seen in the figure, which are consistent with the standard card of Co3O4 (JCPDS No.43-1003). The strong diffraction peaks at 2θ = 31.3°, 36.8°, 38.5°, 44.8°, 59.4° and 65.2° correspond to the (220), (311), (222), (400), (511) and (440) crystal planes of Co3O4, indicating that CoHCC is transformed into Co3O4 after calcination.
[0092] The electrochemical properties of the cobalt tetroxide supercapacitor positive electrode material after calcination of the precursor CoHCC prepared by different proportions of sodium citrate (0.0008 mol, 0.0010 mol, 0.0012 mol) in Example 1-Example 3 were tested in a three-electrode system. The electrochemical test was carried out on a three-electrode system with a concentration of 2M KOH, wherein the three electrodes consisted of a reference electrode Hg / HgO, a platinum electrode and a working electrode; the capacitive performance of the electrode can be characterized by quantitative analysis of the cyclic voltammetry curve, and the method is to perform area integration based on the cyclic voltammetry curve.
[0093] In the process of preparing the precursor CoHCC, the use of surfactant also directly affects the performance of the final product. The present invention selects PVP (polyvinyl pyrrolidone) as the surfactant.
[0094] Figure 4 The four groups of different PVP dosages in Example 2, Example 4, Example 5 and Comparative Example 1 were in the range of 0-0.5V at 50mV s -1 In the cyclic voltammogram under the above conditions, there are intuitive differences in the peak height and area. By comparing 0g PVP, 0.075g PVP and 0.1g PVP, the performance has deteriorated, which shows that the critical micelle concentration has been exceeded, showing an inhibitory effect. 0.05g PVP shows a certain degree of performance improvement.
[0095] In order to show the difference more intuitively, four groups of products were taken at 1A g -1 The discharge curve of constant current charge and discharge under current density is compared, such as Figure 5 As shown. The advantages and disadvantages presented are Figure 5 The results are consistent, both the suppression and enhancement effects are reflected, and the 0.05g PVP has the longest discharge time and shows the best performance again. Figure 6 The AC impedance images of the four groups of materials show that 0.05g PVP shows the lowest resistance level in the high-frequency and low-frequency regions. The addition of PVP improves the electrochemical performance of the cobalt tetroxide supercapacitor cathode material to a certain extent, but when the dosage is excessive, it shows a significant inhibitory effect and the resistance increases accordingly.
[0096] After determining the optimal dosage, the cyclic voltammetry curves at different scan rates and the constant current charge-discharge curves at different current densities were tested. Figure 7 and Figure 8 As shown in the figure, the area and peak height of the CV curve change with the different scan rates, but the curve shape and peak position remain roughly unchanged. Fig. 9 As shown in the figure, the charge and discharge time decreases with the increase of current density. After adding 0.05g PVP, the charge and discharge time decreases with the increase of current density. -1 The specific capacitance under current density also increases from 185F g -1 Increased to 230F g -1 .
[0097] The cobalt tetroxide supercapacitor positive electrode materials prepared by adding 0 g PVP in comparative example 1 and 0.05 g PVP in example 2 were respectively used at 100 mV s -1 The test of 2000 cycles of charge and discharge was carried out at a scan rate of , and the change of retention rate every 100 cycles was recorded, such as Fig.10 shown.
[0098] In the initial stage, the cobalt oxide supercapacitor positive electrode material gradually contacts the electrolyte and the specific capacitance gradually increases. When the number of cycles increases, the specific capacitance begins to decay, and the two groups of materials decay to 82.31% and 91.77% of the initial capacity respectively. It can be seen that the addition of surfactants has improved the life of the active material, and it can still maintain a good level when the number of charge and discharge cycles is large.
[0099] The cobalt oxide supercapacitor positive electrode material (Co3O4) prepared by adding 0.05g PVP in Example 2 was selected to construct an asymmetric supercapacitor with a two-electrode system. The activated carbon YP50 (AC) was used as the negative electrode material to prepare the electrode. The constant current charge and discharge test was carried out in the voltage range of -1~0V. Fig.11 As shown. Calculate AC at 1A g -1 The specific capacitance is 124 F g -1 The mass of the positive and negative electrode materials of the cobalt tetroxide supercapacitor is calculated by the charge balance formula.
[0100]
[0101] Among them, Q + and Q - are the charges of the positive and negative electrodes, respectively, C s+ and C s- are the specific capacities of the positive and negative electrodes, respectively, m + and m - are the masses of the positive and negative electrodes, respectively, ΔV + and ΔV - are the working voltages of the positive and negative electrodes respectively.
[0102] After assembling into an asymmetric supercapacitor, the electrochemical properties of the asymmetric supercapacitor, such as cyclic voltammetry, constant current charge and discharge, and AC impedance, were tested, and the specific capacitance of the material was calculated. The mass of the active material m=m + +m - The specific capacitance of the asymmetric supercapacitor is calculated according to the following formula ( C M ), specific energy density ( E ) and specific power ( P ).
[0103]
[0104]
[0105] in, I , Δ t , m ± and ΔV Represents discharge current (A), discharge time (s), total mass of positive and negative active materials (g) and discharge voltage (V); C M , E and P Represents the specific capacitance of the material F·g -1 Wh kg -1 and W·kg -1 .
[0106] CV curves of cobalt oxide supercapacitor positive electrode materials and activated carbon (AC) are shown in Figure 2. Fig.12 shown.
[0107] The cyclic voltammograms at different scan rates under the optimal voltage window of 1.7V are shown in Figure 2. Fig.13 As shown in Figure 2, the redox peak can be clearly seen due to the redox reaction. Constant current charge and discharge tests at different current densities are shown in Figure 2. Fig.14 As shown, the five curves are roughly symmetrical, and the specific capacity changes are calculated from the images. Fig.15 As shown, the specific capacitance at five current densities is 43.5Fg -1 , 37.6F g -1 , 34.8F g -1 , 31.2F g -1 , 27.7F g -1 The relationship between Co3O4 / / AC energy density and specific power is as follows: Fig.16 As shown, at 1301W kg -1 , 1764W kg -1 , 1821W kg -1 , 2096W kg -1 , 2668W kg -1 At a power density of 1.5W h kg -1 , 15.1Wh kg -1 , 14.0Wh kg -1 , 12.5Wh kg -1 , 11.1Wh kg -1 . Fig.17 The AC impedance curve of Co3O4 / / AC is shown, showing a relatively good impedance level. Fig.18 Shows the 100mV s -1 Capacity retention after 2000 cycles at the scan rate, Fig.19 The CV changes before and after the cycle are shown, and the capacity retention rate is 89.98% after 2000 cycles, demonstrating that the assembled asymmetric supercapacitor has good cycle stability.
[0108] The above results show that when 0.05g PVP is added to the cobalt tetroxide supercapacitor positive electrode material, the specific capacitance increases from 185F g to 20.5F g under the same conditions compared with the one without PVP. -1 Increased to 230F g -1 After 2000 cycles, the capacity retention rate increased from 82.31% to 91.77%, indicating that the addition of surfactant PVP improves the electrochemical performance of the active material. An asymmetric supercapacitor was constructed with the active material containing 0.05g PVP as the positive electrode and activated carbon YP50 as the negative electrode. -1 The maximum energy density is 17.5Wh kg -1 , and when the power is up to 2668.4W kg -1 The energy density is 11.1Wh kg -1 , at 100mV s -1 The capacity retention rate is still 89.98% after 2000 cycles at the same scan rate. These excellent performances may be attributed to the material's ability to provide a large surface area for full contact with the electrolyte, excellent conductivity, and fast charge transfer capability.
[0109] At the same time, the electrochemical properties of the cobalt tetroxide supercapacitor positive electrode materials prepared in Example 2, Example 6, Example 7, Comparative Example 2 and Comparative Example 3 were measured to obtain the following table:
[0110] Table 1 Electrochemical properties of cobalt tetroxide supercapacitor cathode materials
[0111]
[0112] It can be seen from Table 1 that the cobalt tetroxide supercapacitor positive electrode materials prepared in Example 6 and Example 7 have more excellent electrochemical properties. Compared with Example 2, the cobalt tetroxide supercapacitor positive electrode materials prepared in Example 6 and Example 7 have greater specific capacitance, capacity retention rate and energy density.
[0113] The number of devices and processing scales described here are used to simplify the description of the present invention. Applications, modifications and variations of the present invention will be obvious to those skilled in the art.
[0114] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.
Claims
1. A method for preparing a cobalt oxide supercapacitor positive electrode material, characterized in that: The following steps are involved: Step 1, add Co(NO3)2·6H2O, Na3C6H5O7·2H2O and polyvinylpyrrolidone into deionized water and mix well to obtain solution A; Step 2: Add K3[Co(CN)6] to deionized water and mix thoroughly to obtain solution B; Step 3: At room temperature, solution B is added dropwise to solution A, mixed thoroughly and allowed to stand to obtain a pink precipitate. After multiple centrifugation and washing the pink precipitate with deionized water, the pink precipitate is dried in an oven to obtain a precursor CoHCC. Step 4: placing the precursor CoHCC in a muffle furnace, setting a temperature rise program, and keeping the temperature, to obtain a cobalt tetroxide supercapacitor positive electrode material; In the step 4, after the precursor CoHCC is calcined in a muffle furnace, modified NiO is added to the calcined oxide, and the modified NiO accounts for 0-15% of the mass of the precursor CoHCC; the preparation method of the modified NiO includes: S11, dispersing NiO powder in a glucose aqueous solution to obtain a mixed dispersion, wherein the mass volume ratio of NiO powder to the glucose aqueous solution is 0.5-1 g:50-80 mL, and the concentration of the glucose aqueous solution is 0.15-0.3 mol / L; dispersing graphene in deionized water to obtain a graphene dispersion, wherein the mass volume ratio of graphene to the mixed dispersion is 0.1-0.3 g:20-40 mL; S12, mixing the mixed dispersion with a graphene dispersion of half its volume, transferring to an autoclave, setting the heating temperature, pressure and reaction time, cooling to room temperature after the reaction is completed, separating the solid from the liquid to obtain a solid product, and vacuum drying to obtain graphene-modified NiO powder; S13, dispersing graphene-modified NiO powder in deionized water to obtain dispersion A; dispersing nano-MnO2 powder with a particle size of 5-8 nm in dispersion A, adding polyvinyl pyrrolidone, magnetically stirring for 1-3 h, heating to 60-80° C., keeping the temperature for 20-60 min, cooling to room temperature, centrifuging, and vacuum drying to obtain a mixed powder; S14, heat treating the mixed powder by using a static press at 6-8 MPa for 5-10 seconds, specifically comprising: placing the mixed powder in a resistance furnace, heating it to 400-500° C. at a heating rate of 5-10° C. in an argon or nitrogen atmosphere, keeping it warm for 1-3 hours, cooling it to 100-200° C. at a cooling rate of 5-10° C., keeping it warm for 3-6 hours, and finally cooling it with the furnace to obtain modified NiO; In S12, the heating temperature is set to 200-230° C., the pressure is set to 2.5-3.6 MPa, and the reaction time is set to 8-10 h; In the S13, the amount ratio of graphene-modified NiO powder, deionized water, nano MnO2 powder, and polyvinyl pyrrolidone is 1-5 g: 100-250 mL: 0.1-0.5 g: 0.05-0.2 g; The method of adding modified NiO to the oxide obtained by calcining the precursor CoHCC is dry ball milling mixing, using zirconium oxide as grinding balls, the mass of the grinding balls accounts for 1~2.5 times the total mass of the modified NiO and the oxide obtained by calcining the precursor CoHCC, the ball milling time is 1~6h, and the ball milling speed is 500~1000rpm.
2. The method for preparing the cobalt tetroxide supercapacitor positive electrode material according to claim 1, characterized in that: In the step 1, the ratio of Co(NO3)2·6H2O, Na3C6H5O7·2H2O, polyvinyl pyrrolidone and deionized water is 0.6mmol:0.8~1.2mmol:0~0.1g:20~50mL.
3. The method for preparing the cobalt tetroxide supercapacitor positive electrode material according to claim 1, characterized in that: In the step 2, the usage ratio of K3[Co(CN)6] to deionized water is 0.3~0.6mmol:20~50mL.
4. The method for preparing the cobalt tetroxide supercapacitor positive electrode material according to claim 1, characterized in that: In the step 3, the volume ratio of solution A to solution B is 1-2:1-2; The standing time is 12~24h; the drying temperature is 60~90℃.
5. The method for preparing the cobalt tetroxide supercapacitor positive electrode material according to claim 1, characterized in that: In the step 4, the temperature rising program is: heating to 500-800°C at 1-5°C / min, and the holding time is 1-4h.
6. A cobalt tetroxide supercapacitor positive electrode material, characterized in that: The cobalt tetroxide supercapacitor positive electrode material is prepared by the method for preparing the cobalt tetroxide supercapacitor positive electrode material according to any one of claims 1 to 5.
7. A supercapacitor, characterized in that: It includes the cobalt tetroxide supercapacitor positive electrode material as described in claim 6.
Citation Information
Patent Citations
Preparation method and application of high-stability micron-sized cubic cobalt-based prussian blue analogue
CN113200556A